Chinese Students’ Perceptions and Interest in International Careers: An Exploration of Factors Influencing Chinese Masters Students' Career Choices in the UK - Sun, Jiahua (2018)
This research developed and examined a relatively comprehensive scale of Chinese masters students’ interest in an oversea career in UK based on the existing literature. The scale included elements in shaping graduate students’ interest toward the pursuit of international careers: the external (labour markets in the home country and abroad, family pressure to return), experiential (adjustment to the international study experience, exposure and immersion to the international context) and individual (self-efficacy and outcome expectancy) perception. Participants were 173 Chinese masters students who studied in the UK during academic year 2017/2018. The results from the exploratory factor analysis (EFA) suggested a three-component solution with 15 items. The components were labelled as ‘perceived soft skills’, ‘self-efficacy and self-concept’, and ‘employment concerns’. In addition, there were no significant differences in terms of gender and marital status. All subscales showed excellent overall internal consistency and were stable for further development. The implications of theory, practice and future research were discussed.